Petrogenesis of boninitic lavas from the Troodos Ophiolite, and comparison with Izu-Bonin-Mariana fore-arc crust - Wölki, Dominic; Regelous, Marcel; Haase, Karsten; Romer, René; Beier, Christoph (Earth and Planetary Science Letters, 2018)
Supra-subduction zone (SSZ) ophiolites such as the Troodos Ophiolite of Cyprus are thought to have formed at spreading centres close to subduction zones. Similarities in the geochemistry between lavas from SSZ ophiolites and fore-arc lavas from active subduction zones, and the presence of boninites in both, have led to the suggestion that SSZ ophiolites represent fragments of fore-arc crust and mantle, formed during subduction initiation. Here we present major and trace element and Sr, Nd and Pb isotope data for fresh volcanic glasses from a section through the lava pile on the southern margin of the Troodos Ophiolite, and compare these to lavas from the Izu-Bonin-Mariana fore-arc. In Troodos, boninites and tholeiitic basalts are interbedded and were derived from a highly depleted mantle source that was later enriched by both fluids and melts derived largely from subducted sediment, before melting beneath the spreading axis. Troodos boninites differ from Izu-Bonin-Mariana boninites by their greater source depletion, enrichment in Nb by small degree melts, and lack of Zr enrichment relative to Sm. Together with the lack of fore-arc basalts in Troodos, our data imply that the Troodos Ophiolite was formed in a fore-arc location at a back-arc spreading centre that propagated into arc crust. The Troodos Ophiolite was thus not formed during subduction initiation and thus may not be used as analogue for the formation of fore-arc basalts. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Cyprus; boninitic glass; ophiolite; Izu-Bonin-Mariana; subduction initiation; interbedded